Continuous wave technique: temperature changes in different parts of the tooth root (Эндодонтия Today, 2020)
The study investigated the dynamics of temperature changes on the outer surface of the tooth root during root canal obturation using continuous wave technique. Established the safety of this procedure for periodontal tissues, which allows us to recommend it for use on an everyday dental practice.